Pharmacognostic study of 5 medicinal plant species from Western Cape Province (South Africa) for anti-tubercular activity - Bamuamba, Kapinga Benoit (Department of Molecular and Cell Biology, 2014)
Includes bibliographical references (leaves 126-140).